El componente arbóreo en el sistema agroforestal cafetal arbolado en Costa Rica - Espinoza, L. (CATIE, Turrialba (Costa Rica). Dept. de Recursos Naturales Renovables, 2014)
The results are presented an discussed of a study of 117 coffee plantations on 63 estates in the zones of Acosta, Tabarcia and Puriscal. Brief data are given on the socio-economic characteristics, estates and plantation characteristics and coffee production in each area. Three categories of plantations could be distinguished: those with (shade) trees producing one product, two products, or multiple products. The structure and composition of the tree component is described up to ht. 7 m Citrus, Mangifera indica and Musa spp. from 7 to 11 m Inga spp., at 40 m principally Cedrela odorata. Variation in coffee production is described under the 3 plantation categories and in relation to tree cover and products.